Elaborate calibration procedure for cell irradiation at the CAS-LIBB single-particle microbeam - Zhi Wen Hu (2018)
Single-particle microbeam is uniquely capable of precisely delivering a preset number of charged particles to individual cells or sub-cellular targets to be determined in vitro. It is crucial to find a reference point that relates the microbeam's location to the microscope's plane and align individual targets at this reference point for cell irradiation. To choose an appropriate reference point, an approach based on analysing the intensity distribution of fluorescence in a thin scintillator excited by traversing particles is newly developed using the CAS-LIBB single-particle microbeam, which features decisive physical signification and sufficient resolution. As its bonus, this on-line analysis provides precise and fast response to the determination of beam profile and potentially optimizes the microbeam quality by further adjusting hardware setup. © 2006 Chin. Phys. Soc. and IOP Publishing Ltd.